Identification and molecular characterization of peroxiredoxin 6 from Japanese eel (Anguilla japonica) revealing its potent antioxidant properties and putative immune relevancy. (April 2016) - Priyathilaka, Thanthrige Thiunuwan; Kim, Yucheol; Udayantha, H.M.V.; Lee, Seongdo; Herath, H.M.L.P.B.; Lakmal, H.H. Chaminda; Elvitigala, Don Anushka Sandaruwan; Umasuthan, Navaneethaiyer; Godahewa, G.I.; Kang, Seong Il; Jeong, Hyung Bok; Kim, Shin Kwon; et al.
Abstract: Peroxiredoxins (Prdx) are thiol specific antioxidant enzymes that play a pivotal role in cellular oxidative stress by reducing toxic peroxide compounds into nontoxic products. In this study, we identified and characterized a peroxiredoxin 6 counterpart from Japanese eel ( Anguilla japonica ) (AjPrdx6) at molecular, transcriptional and protein level. The identified full-length coding sequence of AjPrdx6 (669 bp) coded for a polypeptide of 223 aa residues (24.9 kDa). Deduced protein of AjPrdx6 showed analogy to characteristic structural features of 1-cysteine peroxiredoxin sub-family. According to the topology of the generated phylogenetic reconstruction AjPrdx6 showed closest evolutionary relationship with Salmo salar . As detected by Quantitative real time PCR (qPCR), AjPrdx6 mRNA was constitutively expressed in all the tissues examined. Upon the immune challenges with Edwardsiella tarda, lipopolysaccharides and polyinosinic:polycytidylic acid, expression of AjPrdx6 mRNA transcripts were significantly induced. The general functional properties of Prdx6 were confirmed using purified recombinant AjPrdx6 protein by deciphering its potent protective effects on cultured vero cells (kidney epithelial cell from an African green monkey) against H2 O2 -induced oxidative stress and protection against oxidative DNA damage elicited by mixed function oxidative (MFO) system. Altogether, our findings suggest that AjPrdx6 is a potent antioxidant protein in Japanese eels and its putative immune relevancy in pathogen stress mounted by live-bacteria or pathogen associated molecular patterns (PAMPs). Highlights: Identification of full length coding sequence of peroxiredoxin 6 from Japanese eel (AjPrdx6). AjPrdx6 resembled 1-Cysteine peroxiredoxin sub family features. Edwardsiella tarda, LPS and poly I:C infections caused significant regulation of AjPrdx6 mRNA expression in liver and spleen tissues. Cell and DNA protecting activity of recombinant AjPrdx6 was examined against oxidative stress.